Is Nefopam Effective in Treating Acute Renal Colic? A Narrative Review - Zainab Al-Shammaa; Mohammed Aladul; Ashraf Aldool; Rima Hijazeen (University of Mosul, 2023)
AbstractBackground: Acute renal colic is a severe and sudden form of loin pain that usually radiates from the flank towards the groin. Acute renal colic is one of the common causes of emergency department admission worldwide. Nefopam has a unique analgesic effect, that differs pharmacologically from nonsteroidal anti-inflammatory drugs, opioids, or paracetamol and has a potential role in multimodal analgesia. Furthermore, studies have found that nefopam has opioid-sparing effects postoperatively following urological surgery, making it a suitable option for urologists and emergency physicians. Aim: This review aims to survey the literature regarding the efficacy of nefopam in treating acute renal colic. Conclusion: This review revealed that the efficacy of nefopam in treating acute renal colic has not been established in any clinical trial, nor has it been included in any international guidelines. Nonsteroidal anti-inflammatory drugs and intravenous paracetamol are first-line agents in the management of acute renal colic.